2019
DOI: 10.1107/s2053230x19010902
|View full text |Cite
|
Sign up to set email alerts
|

Structure of GTP cyclohydrolase I fromListeria monocytogenes, a potential anti-infective drug target

Abstract: A putative open reading frame encoding GTP cyclohydrolase I from Listeria monocytogenes was expressed in a recombinant Escherichia coli strain. The recombinant protein was purified and was confirmed to convert GTP to dihydroneopterin triphosphate (K m = 53 µM; v max = 180 nmol mg−1 min−1). The protein was crystallized from 1.3 M sodium citrate pH 7.3 and the crystal structure was solved at a resolution of 2.4 Å (R free = 0.226) by molecular replacement usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…A study reported that the disruption of GCH1 in S. cerevisiae leads to conditional lethality due to the obstruction of folinic acid synthesis ( Nardese et al, 1996 ). Another study reported that the important role of GCH1 in various physiological processes renders it suitable as a potential anti-infective drug target ( Schüssler et al, 2019 ), which was confirmed when the inhibitors of tetrahydrofolate biosynthesis were successfully able to control a wide variety of microbial and protozoan infections ( Swarbrick et al, 2008 ). However, the function of GCH1 in basidiomycetes has not been investigated so far.…”
Section: Discussionmentioning
confidence: 91%
“…A study reported that the disruption of GCH1 in S. cerevisiae leads to conditional lethality due to the obstruction of folinic acid synthesis ( Nardese et al, 1996 ). Another study reported that the important role of GCH1 in various physiological processes renders it suitable as a potential anti-infective drug target ( Schüssler et al, 2019 ), which was confirmed when the inhibitors of tetrahydrofolate biosynthesis were successfully able to control a wide variety of microbial and protozoan infections ( Swarbrick et al, 2008 ). However, the function of GCH1 in basidiomycetes has not been investigated so far.…”
Section: Discussionmentioning
confidence: 91%
“…In literature, through experiments, it has been proved in H. sapiens , the zinc ion binding residues (Cys‐141, His‐143, and Cys‐212) and residues present near active sites in GTPCH‐I protein [10]. L. monocytogenes has also used H. sapiens GTPCH‐I protein as a template for its structure analysis [37]. So, here we have aligned GTPCH‐I protein of human with GTPCH‐I protein of M. tuberculosis H 37 Rv.…”
Section: Discussionmentioning
confidence: 99%
“…In Listeria monocytogenes , which causes listeriosis (food borne disease) in humans, its folE gene ortholog has been used for drug target. Inhibitor with IC 50 of 13 μM has been used, which is less effective against human GTPCH‐I (IC > 500 μM) [37]. Even in humans, this GTPCH‐I protein is targeted for pain relief [25].…”
Section: Introductionmentioning
confidence: 99%